2016
DOI: 10.2196/mededu.5950
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Analysis of Anesthesiology Podcasts: Identifying Determinants of Success

Abstract: BackgroundAudio and video podcasts have gained popularity in recent years. Increasingly, podcasts are being used in the field of medicine as a tool to disseminate information. This format has multiple advantages including highly accessible creation tools, low distribution costs, and portability for the user. However, despite its ongoing use in medical education, there are no data describing factors associated with the success or quality of podcasts.ObjectiveThe goal of the study was to assess the landscape of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 27 publications
(20 reference statements)
1
25
0
Order By: Relevance
“…Evidence based on opinions and consensus from experts [4-6] suggests that educators should consider credibility and podcast length in their listening choices and development of educational materials [4]. A tool for predicting successful anesthesia podcasts has also recently been developed [7] based on literature review because of a paucity of user rating data. There are also expert-defined quality indicators for social media–based research and educational materials [5].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence based on opinions and consensus from experts [4-6] suggests that educators should consider credibility and podcast length in their listening choices and development of educational materials [4]. A tool for predicting successful anesthesia podcasts has also recently been developed [7] based on literature review because of a paucity of user rating data. There are also expert-defined quality indicators for social media–based research and educational materials [5].…”
Section: Introductionmentioning
confidence: 99%
“…Podcasts in medical education vary in length, and the ideal duration for these has yet to be determined. 25 Given the limited time community-based faculty have available for educational activities, we hypothesized that a short duration would be better received by and more accessible to busy clinicians. Most preceptors listened to at least three podcasts, but only one-quarter of participants listened to all five podcasts.…”
Section: Discussionmentioning
confidence: 99%
“…One study found a total of 22 anesthesiology themed podcasts between 2005 and 2016. 3 This study reported that only 6 out of 22 podcasts were still active in 2016 and that the median longevity of the podcasts was 13 months. Podcasts have been available for a similar amount of time in both emergency medicine and anesthesiology specialties as have competing formats such as audio digests, weblogs (blogs), RSS (really simple syndication) feeds, and wikis.…”
Section: Introductionmentioning
confidence: 88%